PENGARUH VARIASI SUHU KALSINASI TERHADAP SISA DIATAS AYAKAN DAN BAGIAN TAK LARUT SEMEN GEOPOLIMER BERBASIS TANAH NAPA KABUPATEN SOLOK - destaviani, Dine (RC-INSTITUT, 2019)
This research is done to know the benefits of Napa land as the main material in the manufacture of Geopolymer cement. Napa soil derived from the of Solok is natural material with the content of Sio2 and Al2O3 that can be used by the community Around as a remedy for abdominal pain and diarrhea. In this study studied the characteristics of the cement-based geopolymer of Napa soil with variations of temperature calcination, namely the temperature of 500oC, 600oC, 700oC, 800oC against the cement parameters of the remaining sieve and the insoluble part. The results of this study indicated that the characteristics of the remainder above the sieve stated that the smaller the size of cement grains then the wider surface of cement. While the analysis results of the insoluble part of the Geopolymer soil based Napa.Geopolymer Cement has an insoluble part value larger than conventional cement (1.5%-6% max) (SNI 7064:2014) is with an average percentage of 20.5%.